Análisis de las culturas juveniles alternativas en Morelia - Moncada Vargas, Diana (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The philosophy like creative activity that, in general terms he/she invites us to the reflection, to the critic, to the interpretation and understanding of our reality, to inclination of the argument and the dialogue, demand us nowadays to respond to those problematic of our environment; the reflection that we make those and the philosophers you they locate in a society, and the way in that we share this knowledge he/she has a social, coarse implication to remember how the philosophy of the Culture emerges in Mexico, as a thought in and from our sociocultural reality 1. Assisting to the concern of some philosophers Mexicans contemporary 2, about the scarce incidence that has the philosophy in those different elements that they conform our society, in the present investigation approaches one of the socially harmed sectors 3 that integrate and they make culture: those and the youths that it turns to the one excluded in the labor, economic, cultural, educational and political land, it takes them to be identified with models cultural alternative.

La filosofía como actividad creadora que, en términos generales nos invita a la reflexión, a la crítica, a la interpretación y comprensión de nuestra realidad, a través de la argumentación y el diálogo, nos exige hoy día responder a las problemáticas de nuestro entorno; la reflexión que hacemos las y los filósofos se sitúan en una sociedad, y la manera en que compartimos este conocimiento tiene una implicación social, basta recordar cómo emerge la filosofía de la Cultura en México, como un pensamiento en y desde nuestra realidad sociocultural 1 . Atendiendo a la preocupación de algunos filósofos mexicanos contemporáneos 2 , acerca de la escasa incidencia que tiene la filosofía en los diferentes elementos que conforman nuestra sociedad, en la presente investigación abordo uno de los sectores socialmente vulnerados 3 que integran y hacen cultura: las y los jóvenes, que al verse excluidos en el terreno laboral, económico, cultural, educativo y político, los lleva a identificarse con modelos culturales alternativos.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2009-0022; Jóvenes; Identidad; Música; Lenguaje; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/53